2004
DOI: 10.1021/om049818+
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Palladium-Mediated Phosphetane Ring Opening and Pd-to-P Phenyl Migration. Synthesis of a New P-Stereogenic C2-Symmetric Diphosphine Ligand

Abstract: Pd[(S,S)-Et-FerroTANE](Ph)(I) undergoes diastereoselective phosphetane ring opening with concomitant Pd-to-P phenyl migration on mild heating. Cleavage of the resulting palladacycle with acid yields Pd[FerroCHAIN]I2, whose reaction with PhMgBr leads to facile opening of the second phosphetane ring and isolation of a complex of a novel C 2-symmetric ligand with P and C stereocenters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Additional studies by the Marinetti group showed that the ferrocenyl diphosphetanes 4 can also be advantageously used for the asymmetric Ru-catalyzed hydrogenation of -ketoesters [30]. Interestingly this catalytic system was not sensitive to the hydrogen pressure, whereas in the rhodium mediated hydrogenation of dehydroamino acid precursors a [32].…”
Section: Bidentate Bis(phosphetanes)mentioning
confidence: 99%
“…Additional studies by the Marinetti group showed that the ferrocenyl diphosphetanes 4 can also be advantageously used for the asymmetric Ru-catalyzed hydrogenation of -ketoesters [30]. Interestingly this catalytic system was not sensitive to the hydrogen pressure, whereas in the rhodium mediated hydrogenation of dehydroamino acid precursors a [32].…”
Section: Bidentate Bis(phosphetanes)mentioning
confidence: 99%
“…In contrast, the products for Pd are Pd black and Pd(PEt 3 ) 3 . While the analogous Pd alkyne complex Pd(PEt 3 ) 2 (η 2 -PhCCPh) is unknown, many analogues have been reported, indicating that Pd(PEt 3 ) 2 (η 2 -PhCCPh) should exist but must be less stable than the Pt analogue and probably decomposes under the cycloaddition reaction conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Glueck and coworkers reported the synthesis of new chiral phosphine ligands, which are otherwise hard to access, through Pd-mediated P-alkyl/Pd-phenyl exchange from phosphetane rings [68]. In a similar manner to the above-mentioned examples of the P-C bond cleavage from three and five-membered carbon-phosphorus heterocycles, four-membered carbon-phosphorus heterocycles [69] can also undergo facile P-C cleavage to give P-alkyl/Pd-phenyl exchanged palladacycles which can easily be transformed into complexes bearing novel bidentate ligands with both P and C stereogenic centers (Scheme 25).…”
Section: Scheme 24mentioning
confidence: 99%
“…The migration behaviors between M-R (R= alkyl [38,[55][56][57]59,61,66,68], allyl [48][49] and vinyl [89][90][91][92][93][94][95]) and P-Ar have also been studied for a long time. However, during P-Ar/Pd-Me exchange, there has been no evidence for the participation of the phosphonium intermediate [38].…”
Section: Scheme 30mentioning
confidence: 99%